Measuring the Immeasurable: Calculating the Volume of Noah's Ark Using Integrals Can Reveal the Clarity and Sufficiency of the Bible. - Ruth Ririn Vania Siregar; Santri Chintia Purba; Risma Uly Manalu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Mathematics is known as a science that always uses concepts and calculations. Under the pretext that mathematics is just calculations, of course, there is a possibility that there will be a response about mathematics that has nothing to do with the story in the Bible. In fact, based on previous research, it has been stated that one of the two qualities of the Bible is Clear and Sufficient. Considering these two properties, this study aims to prove that the Calculation of the Volume of Noah's Ark using Integral can Reveal the Clarity and Adequacy of the Bible. The research method used is a descriptive research method based on biblical statements that are calculated using integrals. The final result of this study states that the Calculation of the Volume of Noah's Ark using Integral can indeed reveal the Clarity and Sufficiency of the Bible as a form of immeasurable measurement. The meaning is: 1) The clarity of the Bible regarding the Volume of Noah's Ark using Integral can be interpreted and understood with the help of the Holy Spirit. 2) The sufficiency of the Bible regarding the Volume of Noah's Ark using Integral can be interpreted and used as a guideline for every believer's life.